SOCIAL COHESION IN THE REPUBLIC OF MOLDOVA: REALITIES AND PERSPECTIVES - MOCANU, Victor; MALCOCI, Ludmila; MOCANU, Angela (Economy and Sociology, 2021)
Strengthening social cohesion is one of the main directions of the Moldova 2030 strategy. At the same time, the Association Agreement between the Republic of Moldova and the EU stipulates social inclusion, poverty reduction, social cohesion, sustainable development and improving the quality of life as social policy priorities. This article analyzes the theoretical approaches of the concept of social cohesion and presents the results of sociological research on social cohesion in the Republic of Moldova conducted in 2020. The sample includes 1202 respondents and is representative by place of residence (urban / rural), sex, age, level of education. The qualitative study included interviews with 90 experts, representatives of local public authorities, NGOs and the private sector and 3 focus groups. The research was carried out within the project “Training and strengthening social cohesion in the Republic of Moldova in the context of rapprochement with the European Union”. As key aspects of social cohesion were analyzed: self-identification of the degree of belonging of Moldovan citizens to the Republic of Moldova, perceptions of solidarity with other citizens, social trust, participation and inclusion of citizens in political, social and economic processes. The research results showed that the level of cohesion and social solidarity in the Republic of Moldova is quite low. The COVID-19 pandemic has deepened social distancing, uncertainty about the future, poverty and the marginalization of certain groups of the population and has further contributed to lowering the level of social cohesion.